The effect of M-phase stage-dependent kinase inhibitors on inositol 1,4,5-trisphosphate receptor 1 (IP3R1) expression and localization in pig oocytes - Anucha Sathanawongs (2018)
© 2014 Japanese Society of Animal Science. At fertilization, inositol 1,4,5-trisphosphate receptor type 1 (IP3R1) has a crucial role in Ca2+ release in mammals. Expression levels, localization and phosphorylation of IP3R1 are important for its function, but it still remains unclear which molecule(s) regulates IP3R1 behavior in pig oocytes. We examined whether there was a difference in localization of IP3R1 after in vitro or in vivo maturation of pig oocytes. In mouse oocytes, large clusters of IP3R1 were formed in the cortex of the oocyte except in a ring-shaped band of cortex adjacent to the spindle. However, no such clusters of IP3R1 were observed in pig oocytes and there was no difference in its localization between in vitro and in vivo matured oocytes. We next tried to clarify which factor(s) regulates IP3R1 localization, phosphorylation and expression using M-phase stage-dependent kinase inhibitors. Our results show that treatments with roscovitine (p34cdc2 kinase inhibitor) or U0126 (mitogen-activated protein kinase inhibitor) did not affect IP3R1 expression or localization in pig oocytes, although the latter strongly inhibited phosphorylation. However, treatment with BI-2536, an inhibitor of polo-like kinase 1 (Plk1), dramatically decreased the expression level of IP3R1 in pig oocytes in a dose-dependent manner. From these results, it is suggested that Plk1 is involved in the regulation of IP3R1 expression in pig oocytes.